Strategies for Preventing Fishing Vessel Debris Pollution in Tarempa's Coastal Fishing Port, Kepulauan Riau - Amir, Amriansyah; Lestari, Febrianti; Ismail, Khodijah; Syakti, Agung Dhamar (Faculty of Fisheries and Marine, Universitas Riau, 2024)
Research has been conducted on the prevention strategy of fishing vessel waste pollution carried out in April 2024 with the location at Tarempa Coastal Fishing Port. This research aims to formulate a plan for preventing fishing vessel waste at Tarempa Coastal Fishing Port. This research used a survey method with a purposive sampling technique. The data taken in this study are the type and amount of waste from ship activities during mooring, ship maintenance and repair, and maintenance and repair of fishing gear at the Tarempa PPP. The results of observations in the field found that the management done before was only in the form of burning, disposing of garbage in trash cans, hoarding garbage, and some throwing garbage into the sea. Based on the results of the analysis of waste prevention strategies, ten management alternatives were found, including port management needs to establish partnerships with crew members and the community to prevent waste generation at PPP Tarempa, apply rewards for crew members who manage waste well, improve cleaning and waste management facilities at PPP Tarempa, increase routine supervision to prevent waste generation at PPP Tarempa, apply punishment for crew members who pollute the environment, provide counseling and K3 training for crew members at PPP Tarempa, optimize the function of cleaning and waste management facilities at PPP Tarempa.